Brand Color Identity Review of Transportation Apps in Indonesia - Ardani, Nurul Aqmarina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The identity of a brand is known to be represented through color. It is known as brand color identity. Brand color identity makes it easier for consumers to identify the differences in each brand product. So, color plays a role in the consumer brand awareness process. The color as brand identity is also used by transportation applications in Indonesia. They use color as their brand color identity. Thus, this research was conducted to review the brand color identity of the top transportation apps in Indonesia. Aspects of the review include an explanation of the color mode used, the hue size, value, and chroma color used. In addition, the review was also carried out to explain the psychology of the colors behind the colors used.